Structure constraints in Polish and English adjectival synthetic compounds - Wasak, Sebastian (LingBaW. Linguistics Beyond and Within, 2020)
The subject matter of this paper is the external syntax of adjectival synthetic compounds in Polish (e.g. czasochłonny, ciepłolubny, opiniotwórczy, etc.) and English (life-giving, sleep-inducing, far-reaching, etc.). The primary objective of the study is to determine whether -ny/-czy/-ły compounds in Polish and adjectival -ing compounds in English, whose heads appear to be derived from verbs, are deverbal in the sense of Distributed Morphology; that is, whether their external syntax points to the presence of complex verbal structure in their syntactic representation. It is shown that adjectival synthetic compounds in Polish and English behave in a way typical of underived adjectives, being unrestricted in the predicative position and allowing degree modification with very; as such they are not deverbal in the morphosyntactic sense with their syntactic representation lacking the functional heads vP and VoiceP found in deverbal structures. The limited productivity of adjectival synthetic compounds further contributes to their non-eventive status.